Selection and Characterization of Anti-Dengue NS1 Single Domain Antibodies. Issue 1 (December 2018) - Shriver-Lake, Lisa; Liu, Jinny; Zabetakis, Dan; Sugiharto, Victor; Lee, Cheng-Rei; Defang, Gabriel; Wu, Shuenn-Jue; Anderson, George; Goldman, Ellen
Abstract Reliable detection and diagnosis of dengue virus (DENV) is important for both patient care and epidemiological control. Starting with a llama immunized with a mixture of recombinant nonstructural protein 1 (NS1) antigen from the four DENV serotypes, a phage display immune library of single domain antibodies was constructed and binders selected which exhibited specificity and affinity for DENV NS1. Each of these single domain antibodies was evaluated for its binding affinity to NS1 from the four serotypes, and incorporated into a sandwich format for NS1 detection. An optimal pair was chosen that provided the best combination of sensitivity for all four DENV NS1 antigens spiked into 50% human serum while showing no cross reactivity to NS1 from Zika virus, yellow fever virus, tick-borne encephalitis virus, and minimal binding to NS1 from Japanese encephalitis virus and West Nile virus. These rugged and robust recombinant binding molecules offer attractive alternatives to conventional antibodies for implementation into immunoassays destined for resource limited locals.